Общее решение систем нелинейных разностных уравнений с непрерывным аргументом - Пелюх, Г.П. (Український математичний журнал, 2000)
Досаджено структуру загального розв'язку системи нелінійних різницевих рівнянь з неперервним аргументом в околі стану рівноваги. We investigate the structure of the general solution of a system of nonlinear difference equations with continuous argument in the neighborhood of an equilibrium state.